EVALUATION OF RESULTS OF THE FIRST EXPERIENCE OF COMBINED SURGERY FOR VARICOSE VEINS AND KNEE OSTEOARTHRITIS - O. NEMATZODA; A.D. GAIBOV; O.F. SOLIEV; KH.A. TOSHPULOTOV; S.G. ALI-ZADE; A.K. BARATOV (Avicenna Tajik State Medical University, 2022)
Objective: To analyze the results of the first experience of performing simultaneous operations for saphenous varicose veins of the lower extremities and knee osteoarthritis. Methods: The results of simultaneously performed combined phlebectomy and arthroscopic knee surgery in patients with varicose veins (VV) were analyzed. A total of 15 female patients (mean age 52.8±1.9 years) were included in the study. In 5 patients, Clinical Class II, according to the Clinical Etiological Anatomical Pathophysiological (CEAP) classification, published in 1994 for chronic venous disease, was noted, and in 10 - class III. In 13 (86.7%) cases, there was a bilateral dilatation of the saphenous veins; and in 12 patients, there was a combined dilatation of both the Great Saphenous Vein (GSV) and Small Saphenous Vein (SSV). Perforator venous insufficiency was present in 5 patients. Among those examined, in 5 cases, clinical and laboratory findings of the КOA grade II, according to the Kellgren and Lawrence system (1957) for OA classification, were noted, and in 10 patients - grade III. Overweight was observed in 9 patients, and the mean weight was 77.5±3.8 kg. Assessment of the function of the knee joints before and three months after the operation was carried out according to Lequesne's algo-functional index (AFI). Results: The mean diameter of the GSV and SSV was 10.2±0.4 and 6.4±0.4 mm, respectively, and the diameter of insufficient perforating veins was 4.1±0.3 mm. The malleolar circumference before surgical treatment was 37.7±1.5 cm. In all cases, patients had pain and discomfort during the night (n=5 with movement and n=10 without), morning stiffness (n=9), and increased pain when walking a certain distance (n=8) or at the beginning of the movement (n=7). A positive correlation was found between pain and discomfort with age (r=0.53), KOA stage (r=0.70), malleolar circumference (r=0.58) and a negative correlation with body weight (r=-0.55) and recurrence of VV(r=-0.68). All patients complained of walking difficulties, and as a result, their walking distance was reduced. A direct correlation was found between walking distance and body weight (r=0.71), KOA stage (r=0.84), malleolar circumference (r=0.81), pain and discomfort during the night (r=0.66). In addition, in all cases, there was a decrease in daily life activities - the ability to climb one flight of stairs up or down at a moderate effort, squatting or kneeling, and limited ability to walk on uneven ground. The mean operative time of the combined operation's first step (phlebectomy) and arthroscopic knee surgery was 125.5±25.5 and 58.2±10.5 minutes, respectively. The development of postoperative seroma in the wound area was observed in only one case. The average hospital stay was 7.2±1.2 days, and sutures were removed within 10-12 days. A follow-up examination of patients after 1 and 3 months revealed a significant decrease in all the above parameters of Lequesne's AFI and malleolar circumference to 32.0±1.3 cm. Conclusion: Combined phlebectomy with arthroscopic knee surgery in VV comorbid with KOA results in a significant improvement in symptomatic KOA patients with increased walking distance and daily activity with no significant complications.